Intersepsi Pesawat Sipil Ryanair FR4978 oleh Pesawat Militer Belarusia Ditinjau dari Konvensi Chicago 1944 - Sharin Yuniar Permata; Danial Danial; Surya Anom (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Aircraft Interception is an action in which an aircraft moves towards another aircraft in an effort to intercept an aircraft entering national airspace without a flight plan, and an aircraft experiencing communication failure or cannot be identified. Interception actions are allowed in order to protect the sovereign territory of a country, as stated in Article 1 of the 1944 Chicago Convention which recognizes that every sovereign state has complete and complete sovereignty. However, the purpose of interception is limited to determining the identity of the aircraft, directing the aircraft beyond the boundaries of national airspace, directing it away from restricted, restricted or dangerous areas or ordering it to land at a designated airport.. The identification of the problem in this research is, How is the regulation of the interception of civil aircraft by state military aircraft reviewed based on the 1944 Chicago Convention? and What are the legal consequences of the actions of the Belarusian Military Aircraft against the interception of the Ryanair FR4978 Civil Aircraft?This research was conducted using a normative juridical research method. The data collection technique was carried out by literature study and the analysis used in this paper is qualitative analysis by describing or explaining the subject or object of research.The results of this study are first, the regulation of interception actions on civil aircraft is specifically regulated in Article 3 bis of the Chicago Convention 1944 as well as in additional arrangements in Annex 2 to the Convention on International Civil Aviation Rules of the Air which contains instruments or procedures for interception. . Second, the legal consequences received by Belarus for unlawful acts that threaten the security of civil aviation are the imposition of sanctions by the international community in the form of flight restrictions and restrictions on the economic sector, as well as the summons of the Belarusian Ambassador to the European Union